Simulasi Dan Upaya Edukasi Keamanan Siber Menggunakan Situs Web Phishing - Muhammad Ifan Al Aziz; Muhammad Raihan Afarel N.B; Muhammad Fakhri Alauddin; Shelvie Nidya Neyman (TEKTONIK : Jurnal Ilmu Teknik, 2024)
Phishing attacks have become a major threat in the cyber world. Proactive approaches like phishing simulation are now crucial. This simulation enables organizations to gauge users' awareness and vigilance against phishing attacks, as well as identify vulnerable areas in information security. The process begins with creating a clone website from frequently used official sites. This clone replicates the appearance and functionality of the original site to enhance simulation success. Users are invited to access the clone site and prompted to input personal information. Data collected is then analyzed to identify suspicious attack patterns, involving user segmentation based on demographic characteristics. Evaluation measures users' security awareness levels. Simulation results are compiled into detailed reports encompassing findings, analysis, and recommendations. Consequently, organizations can take proactive steps to address phishing threats and enhance user awareness of information security.